Public control of share deals in companies owning agricultural real estate in a comparative perspective - Blajer, Paweł (Przegląd Prawa Rolnego, 2023)
The aim of the research carried out within the framework of the publication is to evaluate, in a comparative perspective, the Polish concepts of public law control of share deals in companies owning agricultural real estate. In its first part, the general shape of the Polish model of control of transactions concerning shares of companies owning agricultural real estate is presented. The second part of the work refers to attempts to subject such transactions to public law control, undertaken in parallel in other European countries, i.e. France, Switzerland and some Austrian federal states. This part also discusses some interesting legislative projects being developed in this respect in some German federal states, which, however, have not, as yet, entered into force. Conclusions drawn from the comparison of Polish and foreign legal regulations, as well as the resulting observations relating to the most serious problems of the solutions adopted in Poland are, in turn, the subject of the concluding remarks.